Experimental methods for inter-module joints in modular building structures – A state-of-the-art review - Lacey, Andrew; Chen, Wensu; Hao, Hong (ELSEVIER, 2022)
This paper presents a state-of-the-art review of the experimental methods for inter-module joints (IMJs) in modular buildings. For the structural response, three levels of study are defined: module (M), frame (F), and joint (J). The joint (J) tests are further classified based on three setups, namely the beam-column (BC) subassemblage with column loading (J/C), the BC subassemblage with beam loading (J/B), and the stub column assembly (J/S). The experimental setups and loading protocols are outlined with reference to the existing literature, and the inherent assumptions and the relative advantages and disadvantages are discussed with the aim of promoting consistency. A case study modular building frame is defined to illustrate the three levels of study (M, F, and J), and the unbraced and braced frames are subjected to lateral loads to demonstrate the effect of bracing on the structural response. The J/C test is shown to be best suited for application to unbraced frames, while the J/S test is more suited to braced frames. Unbraced frames are shown to be vulnerable to failure of the welded beam-to-column connection which can occur in the joint tests before the specimen displacement is large enough to reveal the IMJ behaviour. A summary is given of the existing beam-to-column joint (BCJ) enhancement methods which can strengthen the BCJ and enable measurement of the IMJ behaviour in the tests. The paper concludes with a summary of the experimental methods, recommendations for standardisation, and the key technical challenges and future research directions.